Perbandingan Model Pembelajaran GO CAR (Guided, Orientation, Challenge, Analysis, and Review) dengan Model Pembelajaran GOLD (Guided, Organizing, Leafted, Discovery) terhadap Peningkatan Kemampuan Penalaran Matematika Siswa - Jusniati; A. M. Irfan Taufan Asfar; Paronda, Naimah (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
Based on research conducted at SMA Negeri 15 Bone, it shows that the mathematical reasoning abilities of students at this school are in the low category because the mathematics learning process is still dominated by teachers, which results in most students tending to accept whatever is said by the teacher, being silent and unwilling to express it. questions or opinions. This research is an experimental research with a Quasy Experimental Design research design in the form of Non-Equivalent Control Group Design which aims to find out the comparison between the GO CAR (Guided, Orientation, Challenge, Analysis, and Review) learning model and the GOLD (Guided, Organizing, Leafted) learning model. , Discovery) towards increasing students' mathematical reasoning abilities. The population of this study were all students of class XI MIPA SMA Negeri 15 Bone. Samples were taken using a Non Random Sampling technique with Purposive Sampling type. Samples were taken from two classes, namely XI MIPA 6 as experimental class 1 and class and the GOLD (Guided, Organizing, Leafted, Discovery) learning model for improving students' mathematical reasoning abilities. This can be seen from the data resulting from the hypothesis using the Mann-Whitney test, with a significance value of 0.419 > 0.05, so H0 is accepted and H1 is rejected. Thus, it can be concluded that in this research there is no comparison between the GO CAR (Guided, Orientation, Challenge, Analysis, and Review) learning model and the GOLD (Guided, Organizing, Leafted, Discovery) learning model in improving students' mathematical reasoning abilities at SMA Negeri 15 Bone.